Local gate leakage current induced by inhomogeneous epitaxial growth in AlGaN/GaN high-electron-mobility transistors. (12th February 2016) - Narita, Tomotaka; Wakejima, Akio; Egawa, Takashi
Abstract: We found that inhomogeneous epitaxial growth in a superlattice near a Si substrate creates an area where local leakage current occurs at the interface between an AlGaN surface and a Schottky electrode. Here, electroluminescence (EL) through a transparent gate of an AlGaN/GaN high-electron-mobility transistor enables us to identify the area in the entire gate periphery. Further, the superlattice near the Si substrate supports clear observation of inhomogeneous growth under the EL spots. The energy-dispersive X-ray spectroscopy profile indicates that a Ga-rich layer was grown in the early stage of inhomogeneous area creation.